Carotenoids in Crude Palm Oil (CPO): Content, Antioxidant Activity, and Potential Applications - Alya Azzahra S Nawawi; Efri Mardawati; Selly Harnesa Putri (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Crude palm oil (CPO) is both a lipid commodity and a concentrated source of phytonutrients, particularly alpha-carotene and beta-carotene. This review evaluates carotenoid composition, antioxidant mechanisms, processing effects, and application opportunities using a systematic literature review framework without fabricating PRISMA counts. Commercial CPO generally contains about 500-700 mg/kg total carotenoids, although genotype, fruit maturity, postharvest handling, and extraction conditions cause substantial variation. The conjugated polyene system enables singlet-oxygen quenching and radical interactions, but DPPH, ABTS, FRAP, and ORAC results are not directly interchangeable. Conventional refining, particularly bleaching and high-temperature deodorization, causes major losses through adsorption, isomerization, and oxidation. Red palm oil processing, green extraction, and encapsulation provide routes for food, nutraceutical, cosmetic, natural-colorant, and feed applications. Future work should prioritize bioavailability, controlled clinical studies, product stability, industrial scale-up, and integrated sustainability assessment